Challenges for Privacy with Ubiquitous Sensor Logging - Scott, James (Proceedings of the Pervasive 2008 Workshop on Security and Privacy Issues in Mobile Phone Use, 2008)
In this position paper I discuss some implications for privacy of a future where sensing and logging of sensor data is ubiquitous.